Iran J Pathol 2018
DOI: 10.30699/ijp.14.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor (EGFR) Gene Mutation Analysis in Adenocarcinoma of Lung, the First Report from Iran

Abstract: Background and Objective: Epidermal growth factor receptor (EGFR) gene mutation, especially in exons 18 to 21, is an important predictor of the response rate of lung adenocarcinoma to tyrosine kinase inhibitors. There are variable reports from Asian and European countries, as well as North America, about the frequency of the EGFR mutation in lung adenocarcinoma, yet molecular study about this incidence has been published from Iran. In this study, we investigated the frequency of this mutation in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…The substitution mutation of c.2253A > G was the rarest found in the present work, which accounted for up to 5.8% of all detected mutations. Similar to our results, an in-frame deletion was reported in exon 19 as the most common EGFR mutation comprising up to 71.4% of all mutations in lung adenocarcinoma patients (Shiraz, Iran) ( 18 ). Moreover, in our investigation, two main resistant EGFR -TKI mutations (exon 20 inserts and T790M) were not found that is to consistent with two previous studies conducted in Iran ( 17 , 18 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The substitution mutation of c.2253A > G was the rarest found in the present work, which accounted for up to 5.8% of all detected mutations. Similar to our results, an in-frame deletion was reported in exon 19 as the most common EGFR mutation comprising up to 71.4% of all mutations in lung adenocarcinoma patients (Shiraz, Iran) ( 18 ). Moreover, in our investigation, two main resistant EGFR -TKI mutations (exon 20 inserts and T790M) were not found that is to consistent with two previous studies conducted in Iran ( 17 , 18 ).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the frequencies and nature of driver mutations in NSCLC cases have been shown to be largely distinct, primarily based on ethnicity ( 16 ). Regarding Iran, as a highly multi-ethnic/racial country, there are several reports on the incidence of EGFR mutations in NSCLC patients ( 17 , 18 ). Therefore, evaluating the frequencies of EGFR mutations in different ethnicities in this country is essential.…”
Section: Discussionmentioning
confidence: 99%
“…Original articles were identi ed from Jordan [19], Iran [20,21], Turkey [22][23][24][25][26], Bahrain [27], Iraq [29,30], Lebanon [31][32][33], Morocco [35][36][37], Tunisia [38][39][40], Egypt [41], and Algeria [42]. A multicenter prospective study from Levant (Lebanone, Syria, Palestine, Jordan, Iraq, and Egypt) [34] and a multisite retrospective study from Gulf region (Saudi Arabia, the United Arab Emirates and Qatar) were also identi ed and will part of our analysis [28].…”
Section: Introductionmentioning
confidence: 99%
“…Characteristics of the included studies. 24 eligible studies: 16 (66.6%) in the ME[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and 8 (34.4%) in NA[35][36][37][38][39][40][41][42]. Overall, EGFR mutations were analyzed in 6544 patients with NSCLC [3610 (55.2%) in the ME and 2934 (44.8%) in NA].…”
mentioning
confidence: 99%
See 1 more Smart Citation